Factor XII deficiency - A rare coagulation disorder - Kumar, Rajesh; Gupta, Ashok; Mathur, Priyanshu; Garg, Manisha (Indian Journal of Child Health, 2016)
Severe coagulation factor XII (FXII) deficiency is a very rare, mysterious, and not well-known inherited condition. Unlike other coagulation factor deficiencies, it is usually asymptomatic in most of the cases. Congenital FXII deficiency is the most common cause of an isolated prolongation of the activated partial thromboplastin time in a non-bleeding child or adult; consequently, most patients are detected during a routine pre-operative coagulation study. Surprisingly, it does not lead to abnormal bleeding, but some cases of severe FXII deficiency experiences thrombotic events in their lifetime. There are only a few reports of FXII deficiency in literature. We are reporting a case of congenital FXII deficiency in a 7-month-old child.